PENGARUH TINGKAT KEASAMAN PADA KARAKTERISTIK ZEOLIT ALAM SEBAGAI ADSORBEN AMMONIUM HIDROKSIDA (NH4OH) - Nur Indah Fajar Mukti (Eksergi, 2017)
Natural zeolite is a mineral that are widely available in Indonesia. Among many other benefits, the natural zeolite can be used as an adsorbent to reduce water pollutant caused by ammonia compounds and combination of derivatives. This research aimed to study the effect of different acids on zeolite characterizatics as adsorbent of ammonium hydroxide (NH4OH). The effect of acids addition  on natural zeolite was studied by varying the concentration of H2SO4(0,5 N; 3 N and 5 N) and concentration of H3PO4 (0,5 N; 3 N and 5 N). In this study, zeolite surface was observed by Fourier Transform Infrared (FTIR). Results were showed that the amount of NH4OH adsorbed on H- zeolite has a maximum (23,6 mg/gram zeolit) at 5 N H2SO4. From the NH4OH uptake experiment, it was noted that zeolite obtained from H-Zeolite-H2SO4 has higher NH4OH adsorption capacity than that of zeolite obtained from H-Zeolite-H3PO4. The adsorption capacity of H-Zeolite-H2SO4, H-Zeolite-H3PO4, are 23,6 mg/g and 12,9 mg/g, respectively. FTIR analysis was showed that NH4OH adsorbed on the surface of H- zeolite on Brønsted acid peak.